The Canadian Wheat Board, Socio-economic Vulnerability and the Neo-liberal State - Jane Matthews Glenn (Oñati Socio-Legal Series)
The Canadian Prairies is one of the world's largest breadbaskets. But its location in the centre of the country, far from world markets, increases farmers' vulnerability to the middle-men who ship, handle and market their grain. To protect them, the federal government set up the Canadian Wheat Board in 1935 and gave it monopoly marketing powers in 1943. However, these monopoly powers came increasingly under attack as a market-driven, neo-liberal agenda of free trade, small government, privatization and deregulation gained a hold in the 1980s in Canada, as elsewhere. In 2011, Canada's Conservative-led government adopted the controversial Marketing Freedom for Grain Farmers Act ending the Board's monopoly powers. This legislation is controversial not so much for what it does as for how it was done.